We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
248
3
avatar+283 

Let equation \(x^2+ax+b=0\) and \(x^2+cx+d=0 \)    (a≠c) have the same root \(x\). Please determine this root value using a, b, c, d to represent it. 

 Sep 24, 2018
 #1
avatar+5224 
+4

we can add the two equations to obtain

 

\(2x^2 +(a+c)x+(b+d)=0\\ x^2 + \dfrac{a+c}{2}x+\dfrac{b+d}{2}=0\)

 

\(\text{Now just apply the quadratic formula}\\ r_{1,2} = \dfrac{-\frac{a+c}{2}\pm \sqrt{\left(\frac{a+c}{2}\right)^2 - 2(b+d)}}{2}\)

 

\(\text{we can clean this up a bit}\\ r_{1,2} = \frac{1}{4} \left(\pm\sqrt{(a+c)^2-8 (b+d)}-a-c\right)\)

 

\(\text{If there is only a single shared root }r_1 = r_2\\ \text{if there are no shared roots}\\ (a+c)^2 - 8(b+d)<0\)

.
 Sep 25, 2018
 #2
avatar
+2

Why add the two equations ?

Why not simply subtract one from the other ?

 

Suppose that the first equation has roots p and q and that the second equation has roots p and s,

so that the common root is p.

Then we have

\(\displaystyle (x-p)(x-q)=0 \text{ and }(x-p)(x-s)=0\; .\)

Subtracting the second equation from the first,

\(\displaystyle (x-p)\{(x-q)-(x-s)\}=0\; ,\)

so

\(\displaystyle (x-p)(s-q)=0\; ,\)

showing that  x = p  is the  root of the resulting equation,  \(\displaystyle (\;s \neq q\;)\;.\)

 

So, going back to the original equations and subtracting one from the other,

\(\displaystyle x(a-c)+(b-d)=0\;,\)

\(\displaystyle x=\frac{d-b}{a-c}\; .\)

 

Tiggsy

 Sep 25, 2018
 #3
avatar+5224 
0

you're right though I'd do it as

 

\(x^2+a x+b - (x^2+c x+d) = 0\\ (a-c)x + (b-d) = 0 \\ \forall a \neq c \\ x = \dfrac{d-b}{a-c}\)

Rom  Sep 27, 2018

4 Online Users

avatar